Dynamic behaviors for a (2+1)-dimensional inhomogenous Heisenberg ferromagnetic spin chain system - Douvagai; Amadou, Yaouba; Betchewe, Gambo; Houwe, Alphonse; İnç, Mustafa; Doka, Serge Y.; Almohsen, Bandar (World Scientific Publ Co Pte Ltd, 2021)
We investigate a (2 + 1)-dimensional nonlinear Schrodinger equation (NLSE), which describes the spin dynamics of (2 + 1)-dimensional inhomogeneous Heisenberg ferromagnetic spin chain (IHFSC) with bilinear and anisotropic interactions in the semiclassical limit. Miscellaneous new solitons solutions are obtained through the generalized Riccati equation mapping method (GREMM). Moreover, the effects of homogeneity on the soliton propagation and interaction are discussed. The derived structure of the obtain solutions offers a rich platform to better understand the nonlinear dynamics in the ferromagnetic materials.
Keywords: IHFSC; soliton; generalized Riccati equation mapping method